Safety, Quality, and Religion on the Consumption of Halal Cosmetic Products: Views of Female Muslim University-Students - Talitha Andra Prakasita; Amika Wardana (Universitas Pendidikan Ganesha, 2022)
The awareness of halal cosmetics has been rising among Muslim consumers, particularly female youths in Indonesia, for years. However, it has always been contentious whether this trend is stimulated by the increasing religiosity and Islamic religious understanding among the populace. The study aims to investigate the reasons behind the consumption and its links to the understanding of halal cosmetic products among female Muslim university students, particularly those living in Yogyakarta. For the study, 105 female Muslim students were questioned via a google-form survey, followed by in-depth qualitative phone interviews with 12 of them to gather the required data. The study presents that even though valuing more the safety, quality, and Halal certification status of cosmetic products they have been consuming, female Muslim students prefer to put first the two factors before the third one, followed by others, including the price, adverts, friends’ recommendation. It is revealed that they have shown good knowledge and understanding to look out carefully the ingredients, how to use and safety warning of cosmetic products rather than simply choosing them for religious reasons. Various understanding regarding the halal certification of cosmetic products and its social and religious implications for Muslims have played essential roles in influencing the preference of these female Muslim students.